(untitled) (مجلة البحوث الأكاديمية, 2016)
In this work, a different connection of operational amplifier used to realize a second generation current conveyor CCII. The need of low voltage current conveyor guided to invent various circuits as design of low voltage current conveyor, this paper focused on some topologies from literature, and simulated by orcad 9.2 using CMOS 0.7Um. This connection reveals that the circuits exhibits a good degree of accuracy in its current following capability as is expected of a current conveyor even at the unity gain frequency.